Plant growth-promoting rhizobacteria systemically protect Arabidopsis thaliana against Cucumber mosaic virus by a salicylic acid and NPR1-independent and jasmonic acid-dependent signaling pathway - Ryu, C.M; Murphy, J.F; Mysore, K.S; Kloepper, J.W (The Plant journal : for cell and molecular biology, 2004)
Arabidopsis thaliana ecotype Columbia plants (Col-0) treated with plant growth-promoting rhizobacteria (PGPR) Serattia marcescens strain 90-166 and Bacillus pumilus strain SE34 had significantly reduced symptom severity by Cucumber mosaic virus (CMV). In some cases, CMV accumulation was also significantly reduced in systemically infected leaves. The signal transduction pathway(s) associated with induced resistance against CMV by strain 90-166 was determined using mutant strains and transgenic and mutant Arabidopsis lines. NahG plants treated with strains 90-166 and SE34 had reduced symptom severity indicating that the resistance did not require salicylic acid (SA). Strain 90-166 naturally produces SA under iron-limited conditions. Col-0 and NahG plants treated with the SA-deficient mutant, 90-166-1441, had significantly reduced CMV symptom severity with reduced virus accumulation in Col-0 plants. Another PGPR mutant, 90-166-2882, caused reduced disease severity in Col-0 and NahG plants. In a time course study, strain 90-166 reduced virus accumulation at 7 but not at 14 and 21 days post-inoculation (dpi) on the non-inoculated leaves of Col-0 plants. NahG and npr1-1 plants treated with strain 90-166 had reduced amounts of virus at 7 and 14 dpi but not at 21 dpi. In contrast, no decrease in CMV accumulation occurred in strain 90-166-treated fad3-2 fad7-2 fad8 plants. These data indicate that the protection of Arabidopsis against CMV by strain 90-166 follows a signaling pathway for virus protection that is independent of SA and NPR1, but dependent on jasmonic acid.